Эколого-морфологические развития между двумя близкими видами жаворонков - белокрылым и монгольским - Есилевская, М.А. (Вестник зоологии, 1968)
The comparison of the relative dimensions of bills and jaws of two similar species of larks Melanocorypha leucoptera and M. mongolica shows that as to the jaw apparatus the white-winged lark is less specialized and closer to the initial form than the Mongolian one. It is also confirmed by far less extent of sexual dimorphism in the jaw apparatus of the white-winged lark. At the same time a mating-call flight in these two types is different. The flight of Melanocorypha leucoptera is quick and swift, the flight of M. mongolica is slower, with deep flaps of wings and more manoeuvre. The differences in indices, characterizing the flight organs, correspond to these facts too. In the white-winged lark a wing is more acute and narrow, the relative length of a tail is less and the relative weight of pectoral muscles is more than in Mongolian one. Sexual dimorphism of the flight organs in the both species is of great importance. All this testifies to the fact that the flight organs in these species are specialized in various directions.